The influence of circadian rhythm disruption during Ramadan on metabolic responses to physical activity: a pilot study - Anwardeen, Najeha Rizwana; Naja, Khaled; Almuraikhy, Shamma; Sellami, Maha; Al-Amri, Hadaia Saleh; Philip, Nebu; Tamimi, Faleh; Agil, Ahmed; Elrayess, Mohamed A. (Frontiers in Neuroscience, 2025)
BackgroundCircadian rhythms and sleep patterns are important regulators of metabolic health. During Ramadan intermittent fasting (RIF), the sleep–wake cycles are often disrupted, which can affect physical activity (PA) and related metabolic responses. Limited knowledge is available on how sleep disruption influences PA in the general population during RIF. This pilot study aimed to examine the metabolic responses to moderate PA under normal and disrupted sleep patterns during RIF.MethodsA pilot study was conducted on 12 participants comprising of individuals with normal (n = 5) and disrupted sleep patterns (n = 7). Blood samples were collected, and measurements of clinical traits, cytokines, homeostasis model assessment of insulin resistance (HOMA-IR) and metabolic profiles were performed before and after intervention. Orthogonal partial least square – discriminant analysis (OPLS-DA) and linear regressions were performed to assess metabolic responses to PA during RIF under different patterns.Results and conclusionFasting participants with normal sleep patterns exhibited lower HOMA-IR (β = −0.416, p = 0.047) in response to PA compared to those with disrupted sleep. Additionally, they demonstrated more efficient lipid utilization during PA, characterized by reduced diacylglycerol levels, which could enhance insulin sensitivity and lower the risk of type 2 diabetes. In contrast, fasting participants with disrupted sleep patterns experienced metabolic stress, marked by significant depletion of polyunsaturated fatty acids (PUFAs), monounsaturated fatty acids (MUFAs), and plasmalogens in response to PA. These changes were associated with increased inflammation and oxidative stress, potentially leading to metabolic dysregulation.